The Available Energy Utilization on Earth as an Electrical Resource through Digital Learning Media - Afdal Rezki; Asep Bayu Dani Nandyanto (Research and Social Study Institute, 2022)
The study aims to expand students' knowledge of using SDA (Natural Resources) as an electrical resource and to preserve it with digital literacy. Learning is using powerpoint and simulations using zoom to 24 elementary school students in Perawang, Indonesia, by giving pre-test and post-test. Learning methods are done with online answer question and face-to-face approach limited by pre-test and post-test. Students are working on each of the 10 issues given when pre-test and post-tests are done using Google form. Research indicates from the question given that there is an increase in the value of post-test students after learning. The study provides information that the use of videos and powerpoints can be used as learning media. But the most important thing is how to get students' attention so they can focus on learning. Students are particularly interested in the powerpoint given for using themes and pictures drawn from the game and presence of gifts to students make students focus and enthusiasm about learning increase.